Charakterystyka postawy ciała dzieci w wieku przedszkolnym regionu bydgoskiego = Characteristics of body posture of Bydgoszcz region pre-school children - Monika Katarzyna Mieszkowska; Magdalena Kochanowicz; Michał Garbin; Grzegorz Srokowski; Maja Tomczyk; Elżbieta Piskorska (Kazimierz Wielki University, 2016)
Mieszkowska Monika, Kochanowicz Magdalena, Garbin Michał, Srokowski Grzegorz, Tomczyk Maja, Maciejewski Jerzy. Charakterystyka postawy ciała dzieci w wieku przedszkolnym regionu bydgoskiego =Characteristics of body posture of Bydgoszcz region pre-school children. Journal of Education, Health and Sport. 2016;6(8):637-652. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.61120 http://ojs.ukw.edu.pl/index.php/johs/article/view/3795       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 28.08.2016.     Charakterystyka postawy ciała dzieci w wieku przedszkolnym regionu bydgoskiego Characteristics of body posture of Bydgoszcz region pre-school children   Monika Mieszkowskaa, Magdalena Kochanowicz b, Michał Garbin c, Grzegorz Srokowski c, Maja Tomczyk b, Jerzy Maciejewskid   a Poznan University of Medical Sciences, Poznań, Poznan, Poland   b Jędrzej Śniadecki Academy of Physical Education and Sport in Gdańsk, Gdańsk, Poland c Nicolaus Copernicus University Ludwik Rydygier Collegium Medicum in Bydgoszcz, Bydgoszcz, Poland` d Multi-Municipal Hospital. Dr. E. Warminski in Bydgoszcz, Bydgoszcz, Poland     Key words: faulty postures, body mass index, Lovett testing, corrective gymnastics, Słowa kluczowe: wady postawy, BMI, testowanie Lovetta, gimnastyka korekcyjna, Abstract Introduction. The problem of postures faults concerns on the increasing number of children at younger age and significantly affecting their health. Early diagnosis and its correction allow achieving measurable effects influencing on the quality of life in adulthood. The aim of the study was to assess the selected posture parameters of preschool children. Furthermore the aim was to determine their impact of postures faults on the muscle strength of selected muscle groups. Material/Methods. 50 preschool children, 23 girls and 27 boys (average age 5.34 (± 1.09) years) attending to a non-public kindergarten "Ludzikowo" in Bydgoszcz were examined. The study was conducted in the period from January to March 2013 and consisted of three parts: a questionnaire (diagnostic survey), anthropometric survey (weight, height, BMI), visual analyzes - qualitative method (comparison of posture to the reference), assessment of muscle strength of selected muscle groups using a Lovett testing. Results. The study group showed abnormalities at least in one element of the body posture. In the anterior and lateral projection 90%, in the rear projection 96% of examined children showed the presence of posture faults. A comprehensive body structure and posture analysis according to Staffel method showed that only 62% qualify for the so-called normal pattern of body posture. No statistically significant differences in muscle strength were found in whole group. Conclusions. Utility and the simplicity of proposed assessing methods enables their widespread and early uses in preschool children body posture analyzes. The presence of postures faults in preschool age children does not affect their level of muscle strength.     Streszczenie Wstęp: Problem wad postawy dotyczy coraz większej liczby dzieci w coraz to młodszym wieku i znacząco rzutuje na ich zdrowie. Wczesna diagnostyka oraz ich korekcja pozwala uzyskać wymierne efekty terapeutyczne znacząco niwelując szkodliwość występujących wad oraz ich wpływ na komfort życia w dorosłości. Celem badania była ocena wybranych parametrów postawy ciała dzieci w wieku przedszkolnym oraz określenie wpływu występujących wad na poziom siły mięśniowej wybranych grup mięśni wg. skali Lovetta. Materiał i metody: Badania obejmowały grupę 50 dzieci, 23 dziewcząt i 27 chłopców (w wieku 5,34 (± 1,09) lata), uczęszczających do niepublicznego przedszkola "Ludzikowo" w Bydgoszczy. Badania przeprowadzono w okresie od stycznia do marca 2013. Badanie obejmowało trzy części: kwestionariusz ankiety (met. sondażu diagnostycznego), badanie antropometryczne (pomiar masy ciała, wzrostu, BMI), badanie wzrokowe - metoda jakościowa (porównanie postawy swobodnej z wzorcem), ocena siły mięśniowej wybranych grup mięśniowych przy pomocy testu Lovetta.   Wyniki: Grupa badana wykazywała odchylenia od normy w przynajmniej jednym z obserwowanych elementów postawy ciała. W projekcji przedniej oraz bocznej u 90% dzieci wykazano obecność zaburzeń postawy. W badaniu w projekcji tylnej u 96% badanych wystąpiły odchylenia od prawidłowych wzorców postawy ciała. Całościowa analiza budowy i postawy ciała wg Staffela wykazała, że jedynie 62% kwalifikuje się do tzw. normalnego wzorca postawy ciała. Mimo zaburzeń wzorców postawy nie stwierdzono istotnych statystycznie zaburzeń siły mięśniowej wg. Lovetta. Wnioski: Użyteczność oraz łatwość wykonania zaproponowanych metody oceny postawy ciała pozwala na ich bardzo szerokie zastosowanie i umożliwia wczesną diagnostykę posturalną dzieci przedszkolnych. Obecność wad postawy w wieku przedszkolnym nie rzutuje jeszcze na poziom siły mięśniowej wybranych grup mięśniowych.